Subcutaneous drug supply in the practice of a primary care physician – a literature review - Biesiada, Aleksander; Ciałkowska-Rysz, Aleksandra; Mastalerz-Migas, Agnieszka (Family Medicine & Primary Care Review, 2023)
Subcutaneous administration of drugs can be an important element of a patient’s home therapy with proper treatment initiation and continuation rules. Caring for a dying patient requires an interdisciplinary approach and extensive cooperation between many specialists, including palliative care specialists and primary care physicians. The possibility of treating patients from special risk groups (patients requiring palliative care, elderly patients, debilitated patients) and a wide range of drugs which can be safely prescribed make this method appropriate for use in family practice. The most commonly used medications for symptom control in patients at home can be safely used through this method. There are limitations and even contraindications in the use of high-density and osmolarity drugs, as well as drugs used in chemotherapy. The use of drugs in subcutaneous supply may constitute a smooth transition from the currently used treatment (change of the form of drug administration) or allows for the introduction of new drugs for treatment. It should be noted that for some of the drugs, subcutaneous supply is a supply beyond registration. The most commonly used and recommended puncture at present is a synthetic intravenous puncture of the cannula type. In order to implement subcutaneous supply, it is necessary to know the rules of this form of treatment and their limitations.